Religious and Politics in Argentina : Religious influence on legislative decisions on sexual and reproductive rights - Esquivel, Juan Cruz (2016)
The paper aims at deepening the influence of religious institutions and religious convictions of parliamentarians in the definition of bills related to sexual and reproductive rights at the National Congress in Argentina. Artificial fertilization, sexual identity, decriminalization of abortion, gay-marriage, euthanasia, adoption of children by same-sex couples make up the universe of topics discussed, which in turn, enable a privileged entry to understand the complex linkages between religion and politics. The article concludes with the notion of a subsidiary ´laicity´ as an interpretative framework of triadic link between state, religious institutions and civil society in Argentina.